Work in Primary Health Care and the Covid-19 pandemic: an experience report (Research, Society and Development, 2021)
Introduction: The Covid-19 pandemic has transformed health work and required new forms of care organization and management. In Primary Health Care, many processes were interrupted in order to meet the demands that emerged with the disease, affecting the production of care. Objective: To clarify the work process before and during the Covid-19 pandemic in a PHC unit in the Baixada Fluminense in Rio de Janeiro. Methodology: This is an experience report about the experiences and experiences of a nurse from a Primary Health Care unit in the city of Rio de Janeiro. Results: Different forms of configuration were identified in the field depending on the moment experienced by the professionals, the demands that were absorbed, the logistical capacity and the routines and flows established by the management. Conclusion: It was observed through the experience report how much the pandemic has weakened the positive monitoring of PHC users linked to different lines of care, which can favor in the short, medium and long term the upsurge of diseases previously controlled and contribute to increase in acute pictures.